2015
DOI: 10.1080/03050629.2014.948155
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aid Changes on African Election Outcomes

Abstract: Many African democracies experience highly variable aid flows. This article examines the influence of aid changes on presidential incumbent advantage in Africa. Aid changes influence the odds of incumbents winning reelection, with aid increases helping incumbents, but this effect is only present when the aid change occurs in the year before an election. Aid changes in earlier or later time periods have no influence. Case studies of elections inGhana and Malawi reveal causal mechanisms linking aid changes to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In some regimes, this occurs when aid is appropriated by elites. For example, in Malawi, in the 1990s the country received aid to build schools, but procurement fraud by associates of members of the ruling party meant that few schools were built (Briggs 2015). Instead of funding public goods like schools, this aid was converted into private goods (cash) held by members of the ruling clique and their close associates.…”
Section: Literaturementioning
confidence: 99%
“…In some regimes, this occurs when aid is appropriated by elites. For example, in Malawi, in the 1990s the country received aid to build schools, but procurement fraud by associates of members of the ruling party meant that few schools were built (Briggs 2015). Instead of funding public goods like schools, this aid was converted into private goods (cash) held by members of the ruling clique and their close associates.…”
Section: Literaturementioning
confidence: 99%
“…The fundamental assumption underlying this belief is that foreign aid is distributed to the poor in recipient countries. However, earlier research regarding sub-national distribution of foreign aid in Asia, Latin America, and Sub-Saharan Africa has found no supporting evidence that the poor are the major beneficiaries of foreign economic assistance (Briggs, 2015; Fruttero and Gauri, 2005; Nunnenkamp et al, 2017). Even worse, some other studies show that the allocation of aid is biased toward the wealthy and raises the level of inequality in recipient countries (Abdulai and Hulme, 2014; Bjørnskov, 2010; Boone, 1996; Briggs, 2017, 2018a, b; Layton and Nielson, 2008; Zhang, 2004).…”
Section: Economic Sanctions Sanctions Instruments and Targets’ Inequmentioning
confidence: 95%
“…However, the implementation process of those projects was not properly monitored by relevant authorities. As a result, the considerable number of contractors for those projects were involved in diverse types of corruption and aid money was leaked to the incumbent governments’ election campaigns (Briggs, 2015).…”
Section: Economic Sanctions Sanctions Instruments and Targets’ Inequmentioning
confidence: 99%
“…Comparing the NDC’s vote shares in rural constituencies between 1996 and 2000, Briggs (2012: 617) found that the NDC lost on average five more percentage points in the constituencies that did not receive World Bank–funded electrification. On the other hand, quantitative (see Briggs, 2015) and qualitative evidence suggests that foreign aid can help incumbents win elections. For example, Briggs (2015: 220) presents evidence that education aid was diverted through sham construction contracts and “into campaign spending and cash handouts,” which helped President Muluzi and his party succeed in their bid for reelection in Malawi in the 1999 election.…”
Section: Donor Aid and Electoral Volatilitymentioning
confidence: 99%
“…On the other hand, quantitative (see Briggs, 2015) and qualitative evidence suggests that foreign aid can help incumbents win elections. For example, Briggs (2015: 220) presents evidence that education aid was diverted through sham construction contracts and “into campaign spending and cash handouts,” which helped President Muluzi and his party succeed in their bid for reelection in Malawi in the 1999 election. In a similar vein, Brazys et al (2015) find that Malawi’s president was able distribute the benefits of an aid-supported (Food and Agriculture Organization of the United Nations) fertilizer program in such a way as to boost support for his newly created party in the 2009 legislative elections.…”
Section: Donor Aid and Electoral Volatilitymentioning
confidence: 99%